In memoriam: Jocelyn Cecilia Orchard, 1936–2019 - Tallis, Nigel (Proceedings of the Seminar for Arabian Studies, 2020)
Jocelyn Orchard, who died in August last year following a short illness, was a specialist in the archaeology of the Ancient Near East, with a passion for the grand sweep of history and the early periods of Mesopotamia and Arabia. She was a unique figure in the field of archaeology — in her origins, her enthusiasm and unwavering determination, and in her achievements despite invariably having only very modest resources at her disposal. Latterly an Honorary Research Fellow of the Institute of Archaeology and Antiquity in The College of Arts and Law at the University of Birmingham, she was co-founder and co-Director, with her husband Jeffery Orchard, of The University of Birmingham Archaeological Expedition to the Sultanate of Oman — later renamed The Hajar Project — and worked for thirty-three years investigating sites in the Wadi Bahla, near Bahla town and in the vicinity of Bisya, under the patronage of the Oman Ministry of Heritage and Culture.